ASSOCIATION ANALYSIS BETWEEN MALAT1 RS619581-POLYMORPHISM AND URINARY TRACT CANCER DEVELOPMENT IN UKRAINIAN POPULATION - Stroi, Yelizaveta; Volkohon, Andriy; Moskalenko, Yuliia (Eastern Ukrainian Medical Journal, 2025)
Introduction. A key component in the pathogenesis of oncological diseases is the disruption of genetic and epigenetic regulation of cellular processes, in which long non-coding RNAs play an important role. Of particular significance in the context of cancer development at various sites and its metastasis is the long non-coding RNA MALAT1, which influences tumorigenesis, chemoresistance, and immunotherapy. Therefore, the aim of our study was to investigate the possible association between the genetic marker rs619581 of MALAT1 and the development of urinary tract malignancies. Materials and Methods. The study involved 242 patients with urinary tract cancer (UTC) (101 with clear cell renal cell carcinoma (CCRСC) and 141 with transitional cell carcinoma of urinary bladder (TCCUB)) and 100 individuals without UTC (control group). Among patients with UTC, 97 had metastases, while 145 individuals had no metastases. Genotyping of patients for the rs619581 polymorphism of the MALAT1 gene was performed by real-time polymerase chain reaction using TaqMan assays (TaqMan®SNP Assay C_1060479_10). Statistical analysis of the obtained results was carried out using Prism (version 10.4.1) and R (version 4.4.2) software. Results. The distribution of genotypes for the rs619581 polymorphism in the group of patients with UTC was AA – 216 (89.3%), AG + GG – 26 (10.7%); in the control group, respectively – 96 (96%), 4 (4%) (P = 0.045). The results of the regression analysis of the association of rs619581 genotypes with the development of RCC were close to the level of statistical significance (P = 0.054). And after adjusting for age, sex, smoking habits and BMI, the association became statistically significant: carriers of the minor allele (AG + GG) have a 3.43-fold higher risk of developing RCC than homozygotes for the major allele (AA) (P = 0.037). Among patients with metastases, the distribution of genotypes was as follows: AA – 81 (83.5%), AG + GG – 16 (16.5%), while in individuals without metastases, respectively, AA – 135 (93.1%), AG + GG – 10 (6.9%) (P = 0.02). In patients who are carriers of the minor allele (AG + GG), the risk of developing metastases is 2.67-fold higher than in homozygotes for the major allele (AA) (P = 0.02). Conclusions. In patients with urinary tract cancer, the minor G-allele of the rs619581 polymorphism of the MALAT1 gene is more frequent than in the control group (P=0.039; χ²=4.264). There is an association between rs619581 polymorphism and the development of urinary tract malignancies: carriers of the minor allele (AG + GG) have a higher risk than homozygotes for the major allele (AA) according to multivariable logistic regression, 3.43-fold higher (P = 0.037)). In patients with AG and GG genotypes, the risk of developing metastases is 2.67-fold higher than in homozygotes for the major allele AA (P = 0.02).